UPLC–MS/MS Method Validation for Estimation of Resveratrol in Rat Skin from Liposphere Gel Formulation and Its Application to Dermatokinetic Studies in Rats. (11th September 2021) - Rahman, Mahfoozur; Afzal, Obaid; Panda, Sunil K; Kazmi, Imran; Ali, Ahmed Mahmoud Abdelhaleem; Alossaimi, Manal A; Al-Abbasi, Fahad A; Almalki, Waleed H; Katouah, Hanadi A; Kumar, Vikas; Barkat, Md Abul; Rub, Rehan A; et al.
Abstract: For the quantification of resveratrol (RV) in the Wistar rat skin, an ultra-performance liquid chromatography-mass spectrometric (UPLC–MS/MS) method was developed and validated on ACQUITY UPLC BEH C18 column (1.7 μm). The mobile phase ratio of methanol (A) and 2% formic acid (B) (ratio 10: 90% v/v, 80: 20 v/v) at isocratic elution with flow rate 0.3 mL/min, and run time 3 min was used for analysis. In addition, the use of multiple reaction monitoring (MRM)/ES+ mode to detect the analytes and to track parents to daughter ion transition of 229.17 > 107.04 m/z (time scan 3 min, retention time 1.48) for RV and curcumin as an internal standard shows 369.16 > 176.93m/z (scan time is 2.80 min, retention time is 1.11), respectively. Linearity was observed in the range of 2.5 to 2, 000 ng/mL (R 2 = 0.987). Precision and accuracy on rat skin were within the acceptability range (RE%: ±15; RSD%: ±15). Moreover, it showed a good percentage recovery and found within acceptance limit 90–110%. Lower limit of detection and quantitation for the method observed to be 2.5 and 20 ng.mL −1, respectively. Method application indicated successful determination of dermatokinetics parameters of RV from lipospheres gel and suspension in the rats.